Effect of winnowing on armored bed stability - Chen, Mengli. (2010)
Winnowing failure refers to the entrainment of the finer material from between or under an armored bed, resulting in an irregular lowering of the bed’s elevation. This phenomenon is potentially detrimental to hydraulic structures because of its impact on the foundation. To this end, winnowing induced failure needs to be controlled. The objective of this project is to investigate the mechanism of winnowing failure with an armored bed. Published results have shown that the major factors affecting the threshold of winnowing are the particle property, the flow characteristics and cavity dimension. In this project, the scope is narrowed as to examine the entrainment process of fine particles from rectangular cavities, which is one of the most commonly applied in all the control structure. The project is divided into 4 approaches: numerical modeling, flow visualization test, single particle entrainment test, and time scale analysis. The results of numerical modeling agree well with both flow visualization test and published results. Previous studies on winnowing failure were based on a deterministic model, while in this project, a probabilistic model is employed in both the single particle entrainment experiment and the timescale analysis. High degree of correlation has been shown between the probability of entrainment and time. It is also found that the vorticity field inside a rectangular cavity includes a principal vortex and a secondary vortex. This dual-vortices system influences both the probability of entrainment and the timescale of entrainment.